7(х-у)-4(2у-3х)+4(3х-5у)
При х=-1
При у=-2


7(х-у)-4(2у-3х)+4(3х-5у) При х=-1 При у=-2

Shanmao Shanmao    3   04.11.2021 09:09    10

Ответы
Артём446460 Артём446460  04.11.2021 09:10

.

Объяснение:

7(x-y)-4(2y-3x)+4(3x-5y)=7x-7y-8y+12x+12x-20y=31x-35y=31×(-1)-35×(-2)=-31+70=39

ПОКАЗАТЬ ОТВЕТЫ
J22UKR J22UKR  04.11.2021 09:10

Раскроем скобки и приведём подобные слагаемые:

= 7х - 7у - 8у + 12х + 12х - 20у = (7х + 12х + 12х) - (7у + 8у + 20у) =

= 31х - 35у

при х = -1; у = -2

31 · (-1) - 35 · (-2) = -31 + 70 = 70 - 31 = 39

ответ: 39.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра